Analisis Eksperimental Pengaruh Kombinasi Substitusi Abu Bonggol Jagung dan Serat Fiberglass Terhadap Kuat Tarik Belah Beton - Muhammad Rizki Megantara; Ignatius Sudarsono; Fauzia Mulyawati (LPPM, 2026)
Concrete is a construction material with high compressive strength; however, it exhibits low tensile strength and brittle behavior. Previous studies have extensively investigated corncob ash (CCA) and fiberglass fibers separately, whereas research examining the simultaneous combination of both materials remains limited. This study aims to investigate, through an experimental analysis, the effect of combining CCA substitution as a pozzolanic material with the addition of fiberglass fibers on the splitting tensile strength of concrete, in order to identify the optimum composition capable of enhancing mechanical performance while promoting the sustainable utilization of agricultural waste. The research employed a quantitative experimental method with CCA substitution variations of 0%, 3%, and 6% by cement weight, and fiberglass fiber additions of 0.5%, 1%, and 1.5% by fine aggregate weight. Testing was conducted at curing ages of 7, 14, and 28 days using a total of 126 cylindrical specimens. Characterization of CCA was performed using SEM and EDS analyses, revealing a porous morphology with significant silica content (52.35%), thereby confirming its potential pozzolanic reactivity. The combination of 3% CCA and 1.5% fiberglass fibers produced the highest splitting tensile strength of 2.738 MPa, representing an 18.6% increase compared with normal concrete. A very strong correlation was observed between compressive strength and splitting tensile strength (R² = 0.8419), confirming the effectiveness of the combined use of CCA and fiberglass fibers in simultaneously enhancing the mechanical properties of concrete.